If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -17) + (4x + -12) + (2x + 15) = 180 Reorder the terms: (-17 + 6x) + (4x + -12) + (2x + 15) = 180 Remove parenthesis around (-17 + 6x) -17 + 6x + (4x + -12) + (2x + 15) = 180 Reorder the terms: -17 + 6x + (-12 + 4x) + (2x + 15) = 180 Remove parenthesis around (-12 + 4x) -17 + 6x + -12 + 4x + (2x + 15) = 180 Reorder the terms: -17 + 6x + -12 + 4x + (15 + 2x) = 180 Remove parenthesis around (15 + 2x) -17 + 6x + -12 + 4x + 15 + 2x = 180 Reorder the terms: -17 + -12 + 15 + 6x + 4x + 2x = 180 Combine like terms: -17 + -12 = -29 -29 + 15 + 6x + 4x + 2x = 180 Combine like terms: -29 + 15 = -14 -14 + 6x + 4x + 2x = 180 Combine like terms: 6x + 4x = 10x -14 + 10x + 2x = 180 Combine like terms: 10x + 2x = 12x -14 + 12x = 180 Solving -14 + 12x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 12x = 180 + 14 Combine like terms: -14 + 14 = 0 0 + 12x = 180 + 14 12x = 180 + 14 Combine like terms: 180 + 14 = 194 12x = 194 Divide each side by '12'. x = 16.16666667 Simplifying x = 16.16666667
| 20*2+14=9*n | | 7x(7.5+z)= | | 3x^2-55x-58=0 | | z+(-2z+10)=-z+2(2z-3) | | 2(5x-4)=3x+2 | | W^2-8w-42=0 | | -9(6+u)-2v=-10 | | 2(x-5)-3(x+1)=0 | | (14-3)X(5-2)2= | | 21x+23= | | 8x+1=1+2.4x | | 2(5x-4)=4x+2 | | 5x-(4-3x)=22 | | 2x-4+6x=8(x+1)-12 | | x+22.5=49.25 | | 0.25x+7=3 | | .12=0.6 | | z+100=-8 | | n-3+3=11+2n-6+8 | | (x+4)+7=70 | | 5ln(2z+7)=45 | | a-83=41 | | (3x-1)+5=55 | | 8n^2+3=803 | | 8x-20=3x+9 | | 25m^2+9=73 | | 6x+16=2x+12 | | 4n^2-6=318 | | 9a-b= | | .40x-.20(50+x)=-0.04(50) | | 2k^2+1=163 | | 2x^2+x-48=0 |